Trace metal concentration in freshwater fish organs of Heterotis niloticus from Alaro stream in Ibadan, Nigeria (2014)
Trace metal concentration in freshwater fish organs of Heterotis niloticus from Alaro stream in Ibadan was assessed. Trace metals analyzed were arsenic (As), selenium (Se), cadmium (Cd) and lead (Pb) due to their impacts on human health. Inductively coupled plasma-mass spectrometer (ICP-MS) was used for the analyses of the fish samples while the standard reference material (SRM) for quality assurance was bovine liver from the National Institute of Standards and Technology (NIST).Results show that the mean concentration of As, Se and Pb exceeded the World Health Organization guideline limits and other international standards, while only the muscle and gut did not exceed for Cd. The range of the As in the organs was 0.000-0.963ppm, while the mean concentration was 0.028-0.184ppm with the lowest in the bones and the highest in the gut. The range of the Se in the fish organs was 0.06-1.53ppm, while the highest mean concentration was 1.38ppm in the gills and the lowest was 0.11ppm in the fins. The range of Pb in the organs of H.niloticus was 0.00-14.12ppm, while the highest mean concentration was in the liver and the lowest was in the fins. The study shows that consumption of H.niloticus from Alaro stream is a health risk that must be avoided. It is recommended that a biomonitoring programme be established for regularly monitoring Alaro stream that is impacted by untreated industrial effluents